Differential effects of received social support and mental health symptomology on affect in adults: an Ecological Momentary Assessment study - Tayler E. Truhan; Elyan Aarts; Emily McGlinchey; Talya Greene; Martin Robinson; Cherie Armour (BMC Psychiatry)
Abstract Background Perceived social support is robustly associated with affect and mental health. However, there is a relative lack of consensus regarding the effects of objectively received social support. Extant research is largely cross-sectional and thus potentially limited by recall bias around these time-varied variables. Methods Addressing this, the current study employed Ecological Momentary Assessment (EMA) to examine the relationship between received social support, positive/negative affect, and mental health symptomology (PTSD, depressive, and anxiety symptoms). Trauma-exposed participants (N = 88) completed baseline assessments of mental health, and EMA of positive and negative affect and received instrumental and emotional support at 5 timepoints per day over a 7-day period. Analyses employed mixed effects modelling to assess the effect of received social support on affect over time for adults, and whether this association differed based on mental health symptomology. Clinical trial number: not applicable. Results Results indicated received instrumental and emotional support were positively associated with positive affect. Average received instrumental support was positively associated with average negative affect, whereas recent received instrumental support was negatively associated with current negative affect. Findings did not significantly differ based on levels of mental health symptomology. Conclusions Received emotional and instrumental support may therefore be related to both current and average mood, and be viable targets for intervention particularly for those with previous trauma exposure. Implications for improved understanding of the relationship between received social support and affect are discussed.